2006
DOI: 10.1038/sj.tpj.6500403
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of polymorphisms of ABCB1 and ABCC2 on mRNA and protein expression in normal and cancerous kidney cortex

Abstract: There is increasing evidence that polymorphisms of the adenosine 5 0 triphosphate membrane transporters ABCB1 (P-glycoprotein, MDR1) may affect expression and function, whereas less information is available about the impact of ABCC2 (multidrug resistance-associated protein (MRP2)) single-nucleotide polymorphisms . Particularly, their role in human kidney for drug elimination and in the etiology of renal cell carcinoma is poorly understood. ABCB1 and ABCC2 mRNA and protein expression levels were determined by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 45 publications
(50 reference statements)
7
108
3
Order By: Relevance
“…However, in renal cell cancer tissue we also could not find a significant difference of À24C4T on ABCC2 mRNA expression. 5 Moreover, the findings of this study enlarge the understanding of the previously described reporter gene assay. Usually, reporter gene assays are conducted to investigate the influence of polymorphisms on promoter activity.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, in renal cell cancer tissue we also could not find a significant difference of À24C4T on ABCC2 mRNA expression. 5 Moreover, the findings of this study enlarge the understanding of the previously described reporter gene assay. Usually, reporter gene assays are conducted to investigate the influence of polymorphisms on promoter activity.…”
Section: Discussionmentioning
confidence: 58%
“…7,8 In vitro assays in HepG2 cells revealed a reduced reporter gene activity for the variant construct. 5,7 Interestingly, Caucasian kidney transplant recipients (n ¼ 154) exhibited a significant higher allele frequency for the variant À24T allele than recently investigated healthy Caucasian controls (n ¼ 374) (35.4% vs 18.3%). 9,10 The polymorphism 1249G4A that causes a valin to isoleucin exchange at position 417 in the ABCC2 protein is associated with an increased intestinal efflux and a significant decreased bioavailability of the b-blocker talinolol.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…10,11 The in vivo significance of ABCB1 polymorphisms has been conflicting as to their functional effect on renal P-gp expression. [22][23][24] Since significant linkage exists in the ABCB1 gene, it is important to understand the role of ABCB1 haplotypes in pharmacogenomic association studies. We investigated the LD in our cohort of patients, and while strong LD was observed between SNPs, the degree of LD varied.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies reporting the rs2032582 and rs1045642 T-alleles were associated with lower expression of ABCB1 in term placentas. [27][28][29] In contrast, other studies have reported higher levels of ABCB1 mRNA expression in kidney 30 and heart 31 tissues of carriers of rs2032582 T-and A-alleles compared with G-allele carriers. However, regulation of ABCB1 expression may differ significantly from tissue to tissue.…”
Section: Abcb1 Polymorphisms and Oral Clefts A Omoumi Et Almentioning
confidence: 99%